2015
DOI: 10.1016/j.amjcard.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes for Patients With Severe Symptomatic Aortic Stenosis Treated With Transcatheter Aortic Valve Implantation

Abstract: Transcatheter aortic valve implantation (TAVI) is an established technique for the treatment of severe symptomatic aortic stenosis. Data on long-term TAVI outcomes, both hemodynamic and clinical, in real-world practice settings are limited. We aim to explore the long-term clinical results in patients with severe symptomatic aortic stenosis using multiple catheter-based options: 360 TAVI-treated patients were followed up for ≤5 years. The Medtronic CoreValve was used in 71% and the Edwards SAPIEN in 26%. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…Ewe et al(59) found that frailty phenotype was statistically significantly associated with a 4.2-fold risk in mortality or MACCE, whereas Munoz-Garcia et al(51) did not find such association, likely due to overadjustment for post-procedure ADL dependence. Frailty defined by all other instruments (11, 14, 58, 61) was statistically significantly associated with a 1.9- to 5.6-fold risk in mortality. Only the Green index(14) was developed in a highly representative sample (Appendix Figure 2 panel A).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Ewe et al(59) found that frailty phenotype was statistically significantly associated with a 4.2-fold risk in mortality or MACCE, whereas Munoz-Garcia et al(51) did not find such association, likely due to overadjustment for post-procedure ADL dependence. Frailty defined by all other instruments (11, 14, 58, 61) was statistically significantly associated with a 1.9- to 5.6-fold risk in mortality. Only the Green index(14) was developed in a highly representative sample (Appendix Figure 2 panel A).…”
Section: Resultsmentioning
confidence: 91%
“…We identified 25 studies that evaluated the association of frailty with mortality or functional status at ≥6 months in 18388 patients undergoing major cardiac surgical procedures (9 frailty instruments in 8 studies of CABG or open valve surgery)(41-49) and 5177 patients undergoing minimally invasive cardiac surgical procedures (13 instruments in 17 studies of TAVR)(11-15, 50-61) (Appendix Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…Our initial literature search resulted in total of 3,447 articles. A total of 25 articles [3,[6][7][8][9][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] including total of 21,018 patients were finally included for quantitative synthesis (meta-analysis). Detailed study selection flow is summarized in Supporting Information 1.…”
Section: R Esu L Tsmentioning
confidence: 99%
“…In addition, there has been a recent trend toward a more extensive use of TAV devices in patients with an intermediate to high-risk profile [14]. Although significant experience has been gained and outcomes of TAV implantations are encouraging with a 3-year survival rate of 71.6% [15], various periprocedural complications such as acute kidney injury, vascular complications, pacemaker implantation, paravalvular regurgitation, and major bleeding have been reported [4, 12, 15-17]. Furthermore, due to more constraints on TAV leaflets [18], the long-term durability and safety of TAV devices need to be evaluated and studied carefully [19-21].…”
Section: Introductionmentioning
confidence: 99%